Energy metabolism and behavior in the corticotropin-releasing factor family of peptides - David A. Lovejoy (Frontiers Research Topics, 2015)
Since Hans Selye's seminal work in the 1930s, there have been numerous advances with respect to our understanding of how the nervous and endocrine systems interact to help animals cope with stressors and how chronic stress may adversely impact health. Our modern understanding of stress essentially began in 1954 with the race to discover the hypothalamic releasing factor controlling ACTH secretion and mediating the endocrine response to stressors. Since the isolation of corticotropin releasing factor (CRF) in 1981, interest in CRF has focused not only on its hypophysiotropic function, but also its much broader role in coordinating many of the endocrine, behavioral and autonomic nervous system changes that occur during stress. The goal of this Research Topic is to solicit reviews and general research articles highlighting new research into stress and the hypothalamus-pituitary-adrenal (HPA) axis in the following areas: HPA axis interaction with energy regulating mechanisms during stress; and new studies on the role of CRF and urocortin and urocortins 2 and 3 in behavioral adaptation to stressors.